Toxic Positivity in Adolescents: An Attitude of Always Being Positive in Every Situation - Rahman Pranovri Putra; Auliya Ramadhanti; Anindhita Sasanti; Ahmad Fadil; Nabila Salsyabila (Journal of Psychology and Instruction, 2023)
Toxic Positivity is known as the concept of over-promotion of happiness. This concept believes that staying positive by ignoring negative emotions is the right solution in dealing with problems. This misconception about the concept of staying positive is certainly not by the fact that negative emotions are unavoidable in human life. The aims of this study is to analyze more deeply the meaning of the concept of toxic positivity, in terms of what those who experience toxic positivity think and feel, especially in the context of relationships. This qualitative research with a phenomenological approach focuses on the experiences of individuals with toxic positivity in their social relationship life, starting from what responses, feelings, and impacts arise when getting toxic positivity. Data collection in this study was conducted through interviews. The data obtained were then processed and categorized into the following themes. The findings show that toxic positivity is perceived as an inappropriate motivational response. The toxic positivity response elicits feelings of not being understood, anger, and disappointment, with negative impacts not only physically but also psychologically. The perpetrators are considered to come from individuals who have never experienced similar problems before and lack empathy. In addition, toxic positivity was also found in verbal abuse.